Effects of Changing pH, Incubation Time, and As(V) Competition, on F− Retention on Soils, Natural Adsorbents, By-Products, and Waste Materials - Quintáns-Fondo, Ana; Santás-Miguel, Vanesa; Nóvoa-Muñoz, Juan C.; Arias-Estévez, Manuel; Fernández-Sanjurjo, María J.; Álvarez-Rodríguez, Esperanza; Núñez-Delgado, Avelino (Frontiers in Chemistry, 2018)
The purpose of this work was to elucidate the repercussion of changing pH, incubation time and As(V) competition on fluoride (F-) sorption on forest and vineyard soil samples, pyritic and granitic materials, as well as on the by-products pine sawdust, oak wood ash, mussel shell ash, fine and coarse mussel shell, and slate processing waste fines. To reach this end, the methodological approach was based on batch-type experiments. The results indicate that, for most materials, F- sorption was very high at the start, but was clearly diminished when the pH value increased. However, oak wood ash and shell ash showed high F- sorption even at alkaline pH, and pine sawdust showed low F- sorption for any pH value. Specifically, F- sorption was close to 100% for both ashes at pH <6, and around 70% at pH 10, while for forest soil it was close to 90% at pH <2, and around 60% at pH values near 8. Regarding the effect of incubation time on F- sorption, it was very low for both soils, pyritic material, granitic material and both kinds of ashes, as all of them showed very rapid F- sorption from the start, with differences being lesser than 10% between sorption at 30 min and 1 month of incubation. However, sawdust and slate fines sorbed 20% of added F- in 30 minutes, remaining constant up to twelve hours, and doubling after 30 days. And finally, mussel shell sorbed 20% at 30 minutes, increasing to close to 60% when incubation time was 30 days. This means that some of the materials showed a first sorption phase characterized by rapid F- sorption, and a slower sorption in a second phase. As regards the effect of the presence of As(V) on F- sorption, it was almost negligible, indicating the absence of competition for sorption sites. In view of that all, these results could aid to appropriately manage soils and by-products when focusing on F- removal, in circumstances where pH value changes, contact time vary from hours to days, and potential competition between F- and As(V) could take place.